The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1016/j.actatropica.2014.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Irrigation in the arid regions of Tunisia impacts the abundance and apparent density of sand fly vectors of Leishmania infantum

Abstract: The distribution expansion of important human visceral leishmaniasis (HVL) and sporadic cutaneous leishmaniasis (SCL) vector species, Phlebotomus perfiliewi and P. perniciosus, throughout central Tunisia is a major public health concern. This study was designed to investigate if the expansion of irrigation influences the abundance of sand fly species potentially involved in the transmission of HVL and SCL located in arid bioclimatic regions. Geographic and remote sensing approaches were used to predict the den… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 32 publications
(70 reference statements)
0
14
0
Order By: Relevance
“…This finding agrees with observations on the plasticity and adaptability to environmental changes of P. perniciosus observed in Italy by Tarallo [ 31 ]. Moreover, environmental changes are proved to affect sand fly population and density [ 32 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…This finding agrees with observations on the plasticity and adaptability to environmental changes of P. perniciosus observed in Italy by Tarallo [ 31 ]. Moreover, environmental changes are proved to affect sand fly population and density [ 32 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…We previously demonstrated that the extension of ZVL to Central Tunisia was associated with the geographical expansion of P. perniciosus and P. perfiliewi [ 18 ]. Based on geographical and remote sensing approaches, the density of P. perfiliewi and P. perniciosus was predicted to be moderately high in the arid bio-geographical areas in Central Tunisia [ 19 ]. The results of this study highlighted that abundance of P. perfiliewi and P. perniciosus is associated with the development of irrigated areas [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, in a study conducted in the center of Tunisia, it was demonstrated that Ph. perniciosus was predominant in arid bioclimatic zones and irrigated areas [42,51].…”
Section: Discussionmentioning
confidence: 99%
“…Phlebotomus papatasi, the vector of L. major in Tunisia, is known to be abundant in arid and Saharan regions. Aridity seems to be a limiting factor for its distribution and it was described especially in non-irrigated areas [18,[42][43][44][45]. However, the high number of Ph.…”
Section: Discussionmentioning
confidence: 99%